An efficient distributed mobility management scheme for network mobility - Wagan, A.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Network Mobility (NEMO) is a technology that enables internet services in the public transportation and personal network. To facilitate the internet service in an ongoing vehicle a mobility management protocol shall play a key role. Mobility management is basically responsible for two tasks; node location update of node and service delivery. Present mobility management protocols are incurred with two key issues. First is centralized entity, the central entity provides all intelligence and is responsible for handover process. Therefore, if this entity is fails due to over burden traffic; the whole network is going to suffer. The second issue is related to mobile router; which is frequently moving from one point to another (router visited foreign network). Due to frequently changes in its point of attachment all the running applications will be terminated (session breakup). Therefore; this research work has two objectives. The first objective is to present distributed mobility management architecture to mitigate the central entity issue and the second is to design a handover communication scheme to reduce the long interval, when router changes its point of attachment. Furthermore, an analytical model is developed to analyze the performance of the proposed communication scheme. Â© 2016 IEEE.